Scholars and Gentlemen: A Biography of the Mackerras Family by Joan Priest - Perkins, Elizabeth (LiNQ (Literature in North Queensland), 2016)
E;izabeth Perkins reviews: Joan Priest, Scholars and Gentlemen: A Biography of the Mackerras Family. Brisbane: Boolarong, 1986. 328pp. 25.95.